2019
DOI: 10.1007/s11069-019-03773-3
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of extreme dust storms in east of Iran by the WRF-Chem model

Abstract: Iran, located in the desert belt, is characterized by frequently increasing sand and dust storms, especially in the eastern and southern areas and creating adverse environmental effects. Efficient management of these devastating events requires an understanding of their features. One way to understand the dust phenomenon is to simulate and predict. The general purpose of the article is to simulate severe storms in the southeast of the country (120-day-old winds) due to the weather conditions of the region and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Liu et al, 2020). Some numerical simulations for dust formation and transportation also confirmed that local or regional strong wind was a dynamical factor for dust location (Eltahan & Alahmadi, 2019;Karegar et al, 2019;Hossein et al, 2021;Uno et al, 2001;Yumimoto et al, 2016).…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Liu et al, 2020). Some numerical simulations for dust formation and transportation also confirmed that local or regional strong wind was a dynamical factor for dust location (Eltahan & Alahmadi, 2019;Karegar et al, 2019;Hossein et al, 2021;Uno et al, 2001;Yumimoto et al, 2016).…”
mentioning
confidence: 82%
“…As an extreme weather hazard, regional strong wind is usually associated with the formation of a cyclone in Mongolia and northern China (Y. Liu et al., 2020). Some numerical simulations for dust formation and transportation also confirmed that local or regional strong wind was a dynamical factor for dust location (Eltahan & Alahmadi, 2019; Karegar et al., 2019; Hossein et al., 2021; Uno et al., 2001; Yumimoto et al., 2016).…”
Section: Introductionmentioning
confidence: 88%
“…Weather Research and Forecasting-Chemistry coupled model (WRF-Chem) as a mesoscale meteorology model also has been widely used in forecasting strong dust events [28,30,68,72,73]. Karegar et al [72] simulated the haboob events in east of Iran by the WRF-Chem model.…”
Section: Mesoscale Simulation Methods Of the Wind Field Laden With Ha...mentioning
confidence: 99%
“…Weather Research and Forecasting-Chemistry coupled model (WRF-Chem) as a mesoscale meteorology model also has been widely used in forecasting strong dust events [28,30,68,72,73]. Karegar et al [72] simulated the haboob events in east of Iran by the WRF-Chem model. The model was run for 10 and 30 km spatial resolutions, and results revealed the formation of haboob was affected by local geographical properties especially topography features.…”
Section: Mesoscale Simulation Methods Of the Wind Field Laden With Ha...mentioning
confidence: 99%
“…Additionally, Kargar et al [47] used the WRF-Chem model to numerically simulate extreme dust storms in eastern Iran. Farhadipoue et al [48] studied the severe dust storms in west and southwest Iran by the WRF-Chem model.…”
Section: Introductionmentioning
confidence: 99%